Allopurinol adherence among patients with gout: an Italian general practice database study. Issue 7 (16th February 2015) - Mantarro, S.; Capogrosso‐Sansone, A.; Tuccori, M.; Blandizzi, C.; Montagnani, S.; Convertino, I.; Antonioli, L.; Fornai, M.; Cricelli, I.; Pecchioli, S.; Cricelli, C.; Lapi, F.
Summary Aims Allopurinol is used as long‐term therapy to reduce the occurrence of gout flares. This study estimated the impact of patient adherence to allopurinol on hyperuricaemia (serum uric acid levels, sUA > 6 mg/dl) and the identification of non‐adherence predictors. Methods The Italian Health Search‐CSD Longitudinal Patient Database was accessed to identify outpatients aged ≥ 18 years with gout and prescribed with allopurinol during the years 2002–2011. Patients with a proportion of days covered ≥ 80% were considered adherent to allopurinol. Data on sUA levels over the first year of therapy were categorised in three time‐windows (30–89; 90–149; 150–365 days). Logistic regressions were used to estimate the association between adherence and hyperuricaemia, as well as non‐adherence predictors. Results A total of 3727 patients were included. In the interval 0–29 days, the proportion of patients adherent to allopurinol was 45.9%, while up to 89, 149 and 365 days the percentages were 16.7%, 10.0% and 3.2%, respectively. The proportions of hyperuricaemic patients for each time‐window were 43.1%, 42.4%, 32.6% and 59.0%, 64.0%, 66.4% among adherent and non‐adherent patients, respectively. In the multivariable analysis, adherence was associated with a significant lower risk of hyperuricaemia. The adjusted ORs were 0.49 (95% CI: 0.33–0.73), 0.40 (95% CI: 0.24–0.67) and 0.23 (95% CI: 0.15–0.34) for the first, second and third time‐window, respectively. Patients with hypertension (adjusted OR = 0.64, 95% CI: 0.42–0.99) and history of gout flares (adjusted OR = 0.55, 95% CI: 0.32–0.95) were significantly adherent to allopurinol. Conclusions Adherence monitoring in patients with gout is pivotal to ensure the effectiveness of therapy. To gain a better patient adherence, the communication between physicians and patients should be improved.